Frequency, Clinical Correlates, and Ratings of Behavioral Changes in Primary Brain Tumor Patients: A Preliminary Investigation - Simpson, Grahame K.; Koh, Eng-Siew; Whiting, Diane; Wright, Kylie M.; Simpson, Teresa; Firth, Rochelle; Gillett, Lauren; Younan, Kathryn (Frontiers in Oncology, 2015)
Purpose Few studies have addressed the specific behavioural changes associated with primary brain tumour (PBT). This paper will report on the frequency and demographic/clinical correlates of such behaviours, and the reliability of rating such behaviours amongst people with PBT, family informants and clinicians. The association of behavioural changes and patient functional status will also be discussed. Methods A total of 57 patients with 37 family informants were recruited from two large Australian metropolitan hospitals. Each completed three neuro-behavioural self-report measures. Patients also completed a depression symptom measure. Functional status was defined by clinician-rated Karnofsky Performance Status. Results Patients were on average 52 years old, a median of four months (range 1-82) post-diagnosis, with high grade (39%), low grade (22%) or benign tumours (39%). Patients reported frequency rates of 7-40% across various behavioural domains including anger, inappropriate behaviour, apathy, inertia and executive impairment. The presence of epileptic seizures was associated with significantly higher levels of behavioural changes. Notably, behaviour did not correlate with tumour grade or treatment modality. There was moderate agreement between patients and relatives on the presence or absence of behavioural changes, and substantial agreement between relative and clinician ratings. Depressed patients did not generally report more changes than non-depressed patients. Increases in the relative and clinician-rated behaviour scores were significantly correlated with decreasing functional status in the patient. Conclusions Behavioural changes were a common sequela of both benign and malignant PBT. Larger scale studies are required to confirm these results. The results suggest the importance of including behaviour in brain cancer psychosocial assessments and the need to develop interventions to treat these patients and reduce the burden of care on families.